Kunst na 45 : Kunstkrant uitgegeven door de Vereniging voor het Museum van Hedendaagse Kunst te Gent. - Alene, Ludwig; Balliu, Erik; Bontinck, Dirk; Briers, J.; Bultinck, John; Coeman, Camiel; De Baets, Maria; De Smet, Yves; De Tollenaere, Hugo; De Vogelaere, F.; De Woestijne, H. Van; Derave, W.; et al. (Gent : VMHK (Vereniging voor het Museum van Hedendaagse Kunst) Gent, 1971)
Adami, Valerio ; Appel, Karel ; Bacon, Francis ; Baj, Enrico ; Bogaert, André ; Caille, Pierre ; Christo ; Copers, Leo ; Corneille ; Cortier, Amédée ; D'Haese, Roel ; Dionyse, Carmen ; Elias, Etienne ; Fontana, Lucio ; Gentils, Vic ; Goepfert, Hermann ; Hockney, David ; Van Hoeydonck, Paul ; Huysmans, Camille ; Jones, Allen ; Jorn, Asger ; De Keyser, Raoul ; Landuyt, Octave ; Lichtenstein, Roy ; Lievens, Etienne ; Van Lint, Louis ; Mesens, E.L.T. ; Morris, Robert ; Oldenburg, Claes ; Peire, Luc ; Poliakoff, Serge ; Raveel, Roger ; Raynaud, Jean Pierre ; Raysse, Martial ; Roobjee, Pjeroo ; Rosenquist, James ; De Smet, Yves ; Van Snick, Philippe ; Somerling, Jef ; Tadini, Emilio ; Tsoclis, Costas ; Warhol, Andy ; Wesselmann, Tom ; Wintersberger, Lambert Maria
Nederlands
boek